STUDI KELAYAKAN KUALITAS LAYANAN PENYAMPAIAN KONTEN MULTIMEDIA MELALUI JARINGAN BERKAPASITAS TERBATAS - Jay Idoan Sihotang (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2017)
Rapid technological developments contribute a positive impact on some aspects of life. This research will discuss on transmission of multimedia content in the limited capacity network (up to 5 Mbps), especially to study feasibility of multimedia content delivery quality in limited capacity network. Observation methods include measurement of limited capacity network, and simulating the network to study the feasibility of multimedia content delivery Quality of Service (QoS) over limited capacity network. In our research, multimedia content is transmitted using H264 720p configuration. Simulation that was developed based on network measurement results, and configured with research needs. The results of simulation show that the network condition on testbed network were enough and feasible ni terms of multimedia content delivery quality of service even through limited capacity network.